(untitled) (Research, Society and Development, 2024)
Objective: to analyze the effects of using mobilization as a physiotherapeutic treatment in patients with chronic low back pain. Materials and Methods: This study is characterized by being an experimental qualitative and quantitative approach with an interventional nature and sought to investigate the effects of Neural Mobilization (MN) in patients with Chronic Low Back Pain (CLBP). The sample consisted of eight participants (two men and six women) aged between 45 and 65 years, living in Erechim/RS. Participants underwent a protocol of 10 neural mobilization sessions, carried out twice a week, for 50 minutes each session over five weeks. The assessments carried out were using the Visual Analogue Scale for pain (VAS), Oswestry Disability Index (ODI), Roland-Morris Disability Questionnaire (RMDQ) and the Brazilian Version of the Quality of Life Questionnaire (SF-36). Results: There was a significant reduction in pain intensity (79.61%), improvement in functional disability measured by the RMDQ (from 17 to 10.25) and ODI (from 43% to 20%), in addition to significant improvements in various domains of the SF-36. Conclusion: The findings of this study provide evidence that MN is an effective method for reducing pain and improving the quality of life of patients with CLBP.